(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Haemorrhagic septicaemia (HS) is caused by Pasteurella multocida serotypes B: 2, a Gram-negative coccobacilli bacterium. It causes fatal septicaemia with high mortality in cattle and buffaloes. Disease control and prevention are by effective HS vaccination in animals. A study was conducted on one mixed breed cattle calf for back passage of haemorrhagic septicaemia (HS) seed strain C82. Prior to bacterial inoculation in the calf, Mouse Protection Test (MPT) was conducted to ensure the calf is free from any HS antibody. The calf was injected subcutaneously with 0.5 ml dilutions of 10-3 of the bacteria incubated overnight (approximately 106 CFU/ml). After ±30 hours inoculation, post-mortem was conducted on the calf showing sign of HS. Heart blood and organ samples were collected and cultured on blood agar to determine bacteria purity. Blood and organ samples were also sent to the bacteriology laboratory in VRI for confirmatory tests. The death of the calf is confirmed by re-isolation of Pasteurella multocida Type B. Heart blood collected was processed, freeze-dried and keep as vaccine seed for further usage in vaccine production. Revival of vaccine seed is needed to ensure its pathogenicity and functionality for production purposes.